Integrasi Layanan Bimbingan Konseling dan Pendidikan Islam Dalam Upaya Kontrol Diri Siswa SMA - Retno Purwasih; Muhammad Nikman Naser; Ferisa Prasetyaning Utami (Institut Agama Islam Negeri Bengkulu, 2021)
Abstract: Integration of Counseling Services And Islamic Education In Self-Control Effort Of Senior High School StudentsSelf-control is the ability of individuals to control themselves in behavior, thinking, emotions, and decision making. Self-control can be trained through various approaches, especially counseling guidance and Islamic religious education. The purpose of this study is to determine the level of self-control of high school students and determine the intervention of guidance and counseling services integrated with Islamic religious education. This research is a type of descriptive quantitative research. Data collection was conducted on a sample of 112 people. The results of the self-control measurement score are classified into 5 category levels, namely very high, high, medium, low, and very low. The maximum score of self-control score is 119, the minimum score is 62, the average score is 90.62 and the standard deviation is 12.03. Interventions from the results of measurement and analysis as the basis for a plan for providing guidance and counseling services as well as strengthening student religiosity. The types of services include classical services, group guidance, group counseling, and spiritual guidance.Abstract: Integrasi Layanan Bimbingan Konseling dan Pendidikan Islam Dalam Upaya Kontrol Diri Siswa SMA.Kontrol diri merupakan kemampuan individu untuk mengendalikan dirinya baik dalam berperilaku, berpikir, emosi, dan pengambilan keputusan. Kontrol diri dapat dilatih melalui berbagai pendekatan khususnya bimbingan konseling dan pendidikan agama islam. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kontrol diri peserta didik sekolah menengah atas dan menentukan intervensi layanan bimbingan dan konseling yang terintegrasi dengan pendidikan agama islam. Penelitian ini merupakan jenis penelitian kuantitatif deskriptif. Pengumpulan data dilakukan pada sampel sebanyak 112 orang. Hasil skor pengukuran kontrol diri diklasifikasikan menjadi 5 tingkat kategori yaitu sangat tinggi, tinggi, sedang, rendah, dan sangat rendah. Nilai maksimal skor kontrol diri adalah 119, skor minimal 62, skor rata-rata 90,62 dan standar deviasi sebesar 12,03. Intervensi dari hasil pengukuran dan analisis sebagai dasar rencana pemberian layanan bimbingan dan konseling sekaligus menjadi penguatan religiusitas siswa. Jenis layanan tersebut diantaranya layanan klasikal, bimbingan kelompok, konseling kelompok, dan bimbingan spritual.